Six random specimens of daytime casual urine on different days are sufficient to estimate daily sodium/potassium ratio in comparison to 7-day 24-h urine collections - Iwahori, Toshiyuki; Ueshima, Hirotsugu; Miyagawa, Naoko; Ohgami, Naoto; Yamashita, Hideyuki; Ohkubo, Takayoshi; Murakami, Yoshitaka; Shiga, Toshikazu; Miura, Katsuyuki (Hypertension research, 2014)
The objective of this study was to determine the optimal number and type of casual (spot) urine specimens required to estimate an individual's urinary sodium/potassium (Na/K) ratio. A total of 48 participants, 25 men and 23 women, aged between 25 and 59 years, was recruited from healthy volunteers. The Na/K ratio in each casual urine and 7-day 24-h urine sample was measured. Correlation analysis and the quality of agreement by the Bland and Altman method between casual urine and 24-h urine were analyzed. The mean Na/K ratio of 7-day 24-h urine was 4.3. The mean Na/K ratio of six random specimens of daytime (collected between 09 and 17 hours) casual urine correlated most strongly with the Na/K ratio of 7-day 24-h urine (r=0.87). The bias for the mean Na/K ratio between 7-day 24-h urine and daytime casual urine was almost negligible (0.03), and the quality of agreement for the mean of the six random, daytime casual urine specimens on different days was similar to that of the 2-day 24-h urine samples for estimating 7-day 24-h values. Our findings show that the mean Na/K ratio of six random daytime casual urine specimens on different days was a good substitute for the 2-day 24-h urine Na/K ratio.